2018
DOI: 10.1093/mnras/sty2441
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the ejecta of the GW170817 neutron star merger from its electromagnetic emission

Abstract: We present a simple analytic model, that captures the key features of the emission of radiation from material ejected by the merger of neutron stars (NS), and construct the multi-band and bolometric luminosity light curves of the transient associated with GW170817, AT 2017gfo, using all available data. The UV to IR emission is shown to be consistent with a single ≈ 0.05 M ⊙ component ejecta, with a power-law velocity distribution between ≈ 0.1 c and > 0.3 c, a low opacity, κ < 1 cm 2 g −1 , and a radioactive e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
189
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(209 citation statements)
references
References 79 publications
16
189
4
Order By: Relevance
“…It also does not conflict with the estimation of M ej ∼10 −3 -10 −2 M e for the dynamical ejecta of GW170817 (Abbott et al 2017d;Utsumi et al 2017;Tanaka et al 2017;Matsumoto et al 2018). In a few recent studies, a more precise ejecta mass of M ej ∼0.05M e was estimated when modeling the GW170817 kilonova (Cowperthwaite et al 2017;Drout et al 2017;Kasliwal et al 2017;Kasen et al 2017;Villar et al 2017;Waxman et al 2017). These studies also support the idea that there is enough material being ejected during the NS-NS merger.…”
Section: Numerical Resultssupporting
confidence: 59%
“…It also does not conflict with the estimation of M ej ∼10 −3 -10 −2 M e for the dynamical ejecta of GW170817 (Abbott et al 2017d;Utsumi et al 2017;Tanaka et al 2017;Matsumoto et al 2018). In a few recent studies, a more precise ejecta mass of M ej ∼0.05M e was estimated when modeling the GW170817 kilonova (Cowperthwaite et al 2017;Drout et al 2017;Kasliwal et al 2017;Kasen et al 2017;Villar et al 2017;Waxman et al 2017). These studies also support the idea that there is enough material being ejected during the NS-NS merger.…”
Section: Numerical Resultssupporting
confidence: 59%
“…Several comments are in place here regarding the differences between the Ia SN case discussed in this paper and the kilonova case discussed by Waxman, et al (2018); Waxman, Ofek & Kushnir (2019). First, the characteristic density of the ejecta is some four orders of magnitude lower in the kilonave case, due to the smaller ejecta mass and its higher velocity.…”
Section: Summary and Discussionmentioning
confidence: 77%
“…We use the complete stopping cross section formula, with the logarithmic factor (see figure 2); therefore, the time dependence of our late-time electron heating rate agrees with that obtained by Waxman et al (2019). Waxman et al (2018) interpret a break in the observed bolometric light curve of the GW170817 macronova around ∼ 6 days as the thermalization break, which is a transition of the electron heating rate from the regime ofQ th,e ∝ t −1.3 to ∝ t −2.8 . This scenario requires that the thermalization break occurs at relatively early time and that it is rather sharp.…”
Section: Thermalizationmentioning
confidence: 97%